Decadal variation of rainfall seasonality in the North American monsoon region and its potential causes (2012)
ABSTRACT: This study shows that the North American monsoon system’s (NAMS) strength, onset, and retreat over northwestern Mexico exhibit multidecadal variations during the period 1948–2009. Two dry regimes, associated with late onsets, early retreats, and weaker rainfall rates, occurred in 1948–70 and 1991–2005, whereas a strong regime, associated with early onsets, late retreats, and stronger rainfall rates, occurred in 1971–90. A recovery of the monsoon strength was observed after 2005. This multidecadal variation is linked to the sea surface tem- perature anomalies’ (SSTAs) variability, which is a combination of the Atlantic multidecadal oscillation (AMO) and the warming SST trends. These SST modes appear to cause an anomalous cyclonic circulation and enhanced rainfall over the southeastern United States and the Gulf of Mexico, which in turn increases the atmospheric stability over the monsoon region. However, these SST modes cannot fully explain the circulation and rainfall anomalies observed during the early-retreat monsoons. An expansion of the North Atlantic surface high (NASH) in recent decades also contributes to the anomalous circulation associated with the early retreats of the NAMS. A northwestward expansion of the NASH further enhances the anomalous cyclonic circulation and rainfall over the southeastern United States and the Gulf of Mexico. Its associated northwestward shift of the subtropical jets over the western United States enhances subsidence over the NAMS region. The combined effects of the AMO, the warming trends, and the NASH expansion on atmospheric circulation contribute to a stronger and more persistent earlier retreat during the recent dry regime (1991–2005), while the earlier dry regime (1948–70) appears to be only influenced by the positive phase of the AMO.